COMBINING SYSTEM DYNAMICS AND DISCRETE EVENT SIMULATIONS - OVERVIEW OF HYBRID SIMULATION MODELS - Jovanovski, Bojan; Minovski, Robert; Voessner, Siegfried; Lichtenegger, Gerald (Journal of Applied Engineering Science, 2012)
Simulation and modelling has been widely accepted as one of the most important aspects of the Industrial engineering. The application and use of simulation models has grown exponentially since the 1950’ until today. Over the years, the complexity of the simulated aspects has been adapted to the complexity of the analysed cases which has risen proportionally too. That is why techniques used many years ago, can often not give an adequate representation of the real world any more. For that reason, we propose to use hybrid simulation models, which are a combination of simulation paradigms in order to cope with this problem. In this paper, we will give an overview of selected researches and applications with an emphasis on Discrete Event Simulation and System Dynamics, as one of the core simulation based techniques in that area. Key words: Hybrid, Simulation, Model, System Dynamics, Discrete-event simulation